Kesan Pendidikan Keusahawanan dan Halangan Keusahawanan Terhadap Niat Keusahawanan di Kalangan Pelajar-Pelajar Pendidikan Tinggi - Iskandarini, Sutadi (2011)
This study investigated the relationship of entrepreneurship education and entrepreneurial intention. This study also aimed to determine the mediating effect of entrepreneurial barriers on the relationship between entrepreneurship education and entrepreneurial intention. To answer the research objectives, a total of 22 hypotheses were formulated. The research design employed the questionnaire survey method in collecting the data. The population was students from eight faculties from the Universitas Sumatera Utara who took and completed the entrepreneurship subject. A total of 300 usable questionnaires were obtained from the survey. The questionnaire items were earlier tested for validity and reliability. The data collected were then analysed by using Structural Equation Model (SEM). This statistical method was employed since it correlates variable indicators and latent indicators simultaneously. The finding shows the existence of inverse relationship between entrepreneurship education and entrepreneurial intention. This indicates that the higher the entrepreneurship education among the students the lower their entrepreneurial intention is. The dominant factor in the entrepreneurship education indicator is the facilitator who delivers entrepreneurship education subject while the dominant factor for the entrepreneurial barriers is the strong confidence. The finding also shows that entrepreneurial barriers did not provide any mediation effect on the relationship between entrepreneurship education and entrepreneurial intention. This study contributes to a theoretical framework which shows the effect of entrepreneurship education factors on the entrepreneurial intention of students in the higher education institutions. This study concluded with a discussion on theoretical and policy implications, the study limitation and suggestions for future research.